The Role of the Education Office in Implementing Computer-Based National Assessments for Education Quality Assurance in Mojokerto District - Ma'Fazah, Hikmatul; Asrohah, Hanun (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2025)
This article discusses the role of the Education Office in the implementation of the Computer-Based National Assessment (ANBK) as an effort to guarantee the quality of education in Mojokerto Regency. The Mojokerto Regency Education Office as a government institution that focuses on the implementation of some affairs in the field of education. This study aims to see how much the role of the Education Office in the implementation of the Computer-Based National Assessment towards ensuring the quality of education in Mojokerto Regency. The research method uses qualitative descriptive, using the case study method. The results of the study indicate that the Mojokerto Regency Education Office has played an active role in the implementation of this ANBK, where the Mojokerto Regency Education Office acts as a mediator, as a supervisor and companion, as well as a data processor. The Mojokerto Regency Education Office continues to strive to improve the quality of education in the Mojokerto area. This study is expected to produce applicable input to support the improvement of the quality of education in Mojokerto Regency.